THE RESULTS OF THE CLUSTER ANALYSIS OF VEGETABLE PRODUCERS ON THE EXAMPLE OF THE KHERSON REGION, UKRAINE - Kudrynetskyi , Rostyslav; Dnes , Viktor; Krupych , Stepan; Krupych , Oleh (Collection of scientific papers «ΛΌГOΣ», 2023)
The size of the area of vegetable crops in agricultural enterprises depends on their production direction (specialization), natural growing conditions, the availability of labor and vegetable sales markets, provision of specialized equipment, vegetable storage facilities, etc. Vegetable production requires a significant amount of labor for weeding, harvesting, etc. Vegetable production is difficult to transport, perishes quickly, and therefore needs to be quickly collected and sent for sale. One of the important factors affecting the level of efficiency of commercial vegetable production is the degree of concentration of vegetable production in agricultural enterprises.